ANALISIS PERGESERAN BAHASA TOLITOLI DALAM INTERAKSI MASYARAKAT DI DESA AUNG KECAMATAN GALANG KABUPATEN TOLITOLI (KAJIAN SOSIOPRAGMATIK) - Afifah Istiqomah , (Journal of Innovation Research and Knowledge, 2026)
This study aims to describe the forms and characteristics as well as the factors that cause language shifts in community interaction in Aung Village, Leok Soga hamlet, Galang District, Tolitoli Regency. This study is based on the results of initial observations that people no longer use the Tolitoli regional language in communication, both among children, adolescents, youth/women and adults/parents. The type of research is qualitative descriptive. The data collection technique uses observation, interview, observation and recording techniques as well as data documentation and analysis, namely data triagulation. The results of the study show that based on the form and characteristics, the data obtained by the researcher from community interaction in Aung Village, Leok Soga hamlet, amounted to 10 data from 53 speeches, consisting of the use of speech among children aged (5-12 years), namely as many as 3 data with 15 speeches, while the use of speech among adolescents aged (13-15 years) as much as 1 data that had 2 speeches, Subsequently, the use among youth/women aged (16 – 18 years) as many as 3 data that had 19 speeches, and the use among adults/parents aged (25 and above) as many as 3 data that had 17 speeches. This is because there is a variety of speech in the interaction of people from various dialect tribes. There are those who use the first language or mother tongue called Monolingual (B1), speech that has become subordinate bilingual (B1 – B2), if they have been domineered for some time then their language has become Blingualism (B1 – B2) or equivalent, and finally their language becomes Mobilingual or second language (B2), while the mother tongue they have left behind. Other causative factors are due to population movement/migration, economy, schools and demographicsThus, it can be said that there is no assurance that the Tolitoli regional language's identification symbol will be preserved in the future., preserved among the people of Aung Village, Leok Soga hamlet, but increasingly displaced by the existence of non-formal Indonesian (Malay) which has bilingual and miltilingual languages from various ethnic dialects.